Kumāunnī loka sāhitya kī prshṭhabhūmi - Pāṇḍeya, Trilocana, 1930- (Sāhitya Bhavana, 1979)
Study on the origin, development, and historical background of folk literature in Kumauni, a central Pahari dialect spoken in Kumaun, mountainous district of Uttar Pradesh.